65 The CHA2DS2VASC Risk Score Appropriately Risk Stratifies Patients Prior to Atrial Fibrillation Ablation and Reduces The Requirement for Trans-Oesophageal Echocardiography. (3rd June 2016) - Atkinson, Charlotte; Hinton, Jonathan; Gaisie, Edmund; Rakhit, Dhrubo; Roberts, Paul; Yue, Arthur; Shah, Benoy
Abstract : Background: Prior to atrial fibrillation (AF) ablation, many centres advocate trans-oesophageal echocardiography (TOE) to exclude left atrial appendage (LAA) thrombus. Patients undergoing AF ablation are usually anticoagulated, thus making the presence of thrombus unlikely. This study aimed to determine whether the CHA2 DS2 VASc scoring system could be used for risk stratification to identify patients that do not require TOE prior to AF ablation. Methods: In this single centre retrospective study, primary and secondary care databases and electronic patient records were searched to identify patients that had undergone TOE prior to AF ablation and also correlated with catheter lab records. Patient demographics, CHA2 DS2 VASc score, TOE findings and anticoagulation status were collected. Results: Over a 7 year period (2008–2014), 346 patients underwent TOE prior to AF ablation – 14 patients were excluded due to incomplete data, leaving 332 patients (age 57 ± 10 years; 74% male). There were 227 (68%) patients with paroxysmal AF and the remainder had persistent AF. CHA2 DS2 VASc scores of 0, 1, 2 and >2 were found in 39%, 34%, 15% and 12% patients respectively. There were 31/113 (27%) patients whose score was 1 due to female gender. The prevalence of LAA thrombus was 0.6% (2 patients). One patient with thrombus (score=4) had hypertrophic cardiomyopathy, mild LV dysfunction and sub-therapeutic INR (1.5) at time of TOE whilst the other patient (score=2) was female with hypertension and mild LV dysfunction. No patients with a score of 0 or 1 had LAA thrombus. Conclusions: Patients classed as low riskby theCHA2 DS2 VASc score (score of 0–1) do not require a pre-ablation TOE to screen for LAA thrombus provided they have been anticoagulated with a therapeutic INR. This would lead to a significant reduction in healthcare expenditures by reducing unnecessary TOE tests and improve patient experience by avoiding TOE.